Association between non-traumatic vertebral fractures and adjacent discs degeneration: a cross-sectional study and literature review - Takegami, Norihiko (BMC Musculoskelet Disord, 2020)
BACKGROUND: Previous clinical studies reported that thoracolumbar vertebral fractures (VFs) associated with high energy spine trauma cause adjacent intervertebral disc (IVD) degeneration; however, the effect of non-traumatic VFs on the progression of adjacent disc degeneration remains to be determined. The purpose of this study was to examine the association between non-traumatic VFs and degenerative changes of adjacent IVDs. METHODS: Ninety-eight consecutive patients undergoing spinal surgery were included in this study. VFs were semi-quantitatively evaluated by lateral lumbar radiography. Five hundred eighty-eight vertebral bodies (from T12 to L5) and 486 discs (from T12/L1 to L4/L5) were analyzed. The degree of IVD degeneration was evaluated by magnetic resonance imaging (MRI) and classified into two groups according to Pfirrmann’s classification. Grades I, II and III were defined as the early stage of IVD degeneration and Grades IV and V as the advanced stage. Intradiscal vacuum phenomena (VPs) were evaluated by computed tomography. Adjacent IVDs were categorized according to the locations of VFs (superior, inferior, and bilateral). Associations between the presence of VFs and the extent of IVD degeneration or the presence of VPs were statistically analyzed. RESULTS: IVDs adjacent to VFs were identified in 115 IVDs (31.1% of total; superior: 11.4%, bilateral: 8.6%, inferior: 11.1%). The presence of VFs was significantly associated with MRI grades of adjacent IVD degeneration (P < 0.01) and the prevalence of VPs within adjacent IVDs (P < 0.01). From logistic regression analysis, age, disc level, and VFs were independent related factors for disc degeneration (P < 0.05). CONCLUSION: This study showed that VFs were an independent related factor for adjacent disc degeneration and occurrence of intradiscal VPs. VFs may affect the micro-environment of adjacent IVDs, leading to disc degeneration and disc rupture.